2021
DOI: 10.1093/petrology/egab068
|View full text |Cite
|
Sign up to set email alerts
|

The Timing, Duration and Conditions of UHT Metamorphism in Remnants of the Former Eastern Gondwana

Abstract: Early Palaeozoic ultrahigh-temperature (UHT) metamorphism in eastern Gondwana was an event that started with Gondwana amalgamation at c. 580 Ma and lasted at least 50 Myr. Sapphirine + quartz, Mg–Al granulites preserve a record of the timing and duration of the event along the metamorphic belt. U–Th–Pb dating of zircon and monazite shows that metamorphism peaked almost simultaneously in Antarctica (554.0 ± 4.7 Ma), Sri Lanka (555.5 ± 4.6 Ma), southern India (548.1 ± 8.1 Ma) and Madagascar (550.6 ± 6.0 Ma), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 174 publications
0
8
0
Order By: Relevance
“…The unimodal age distribution from this study, the Madurai and Trivandrum blocks (Figure 14a–c) with ages clustered around 600–500 Ma, is suggestive of a late Neoproterozoic to Cambrian long‐lived metamorphism in both the blocks (Dev et al, 2022; Kadowaki et al, 2019; Tiwari & Sarkar, 2020). Although, monazite ages from Sri Lanka show bimodal distribution (Figure 14d), the older ages (peaking c. 650 Ma) are associated with prograde evolution, and the younger ages (peaking c. 480 Ma) are associated with retrograde growth (Dharmapriya et al, 2015; Durgalakshmi et al, 2021; Sajeev et al, 2010), further indicating a prolonged late Neoproterozoic to Cambrian metamorphic cycle. Texturally controlled in situ dating of the monazite from SGT strengthens the evidence for such prolonged metamorphic cycles (~ > 100 MYr) where UHT conditions are sustained for >40 MYr (Clark et al, 2015; Dev et al, 2022; Kadowaki et al, 2019; Li et al, 2020; Tiwari & Sarkar, 2020) and are in line with our observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unimodal age distribution from this study, the Madurai and Trivandrum blocks (Figure 14a–c) with ages clustered around 600–500 Ma, is suggestive of a late Neoproterozoic to Cambrian long‐lived metamorphism in both the blocks (Dev et al, 2022; Kadowaki et al, 2019; Tiwari & Sarkar, 2020). Although, monazite ages from Sri Lanka show bimodal distribution (Figure 14d), the older ages (peaking c. 650 Ma) are associated with prograde evolution, and the younger ages (peaking c. 480 Ma) are associated with retrograde growth (Dharmapriya et al, 2015; Durgalakshmi et al, 2021; Sajeev et al, 2010), further indicating a prolonged late Neoproterozoic to Cambrian metamorphic cycle. Texturally controlled in situ dating of the monazite from SGT strengthens the evidence for such prolonged metamorphic cycles (~ > 100 MYr) where UHT conditions are sustained for >40 MYr (Clark et al, 2015; Dev et al, 2022; Kadowaki et al, 2019; Li et al, 2020; Tiwari & Sarkar, 2020) and are in line with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Our data from the semipelites and charnockites of the MB suggest a clockwise P-T evolution with an inferred peak at f). All these findings point to regional UHT metamorphism during late Neoproterozoic to Cambrian with clockwise P-T evolution, characteristic of metamorphism in a convergent plate-boundary setting (Durgalakshmi et al, 2021;Harley, 2016;Kelsey & Hand, 2015). In such a collisional orogenic setting, UHT conditions can be attained through magmatic underplating, post-collisional slab breakoff and delamination, and lithospheric extension, as well as through conductive heating from HPE in an crust (Reviewed in Harley, 2016;Lei & Xu, 2018).…”
Section: Heat Source and Geodynamic Implicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent study has revealed that transitional-zone rocks also attained higher-T granulite facies conditions at the pressures of ~1.1 GPa (Suzuki and Kawakami, 2019). Furthermore, many geological, petrological and geochemical studies have been conducted recently, especially in the granulite-facies zone, that emphasize long-lived high temperature metamorphism with partial melting and possible magma generation at UHT conditions (e.g., Durgalakshmi et al, 2021;Carvalho et al, 2023). However, data from the amphibolite-facies zone are comparatively scarce.…”
Section: Lützow-holm Complexmentioning
confidence: 99%
“…The Madurai Block comprises granulite-facies rocks that are mostly metaigneous, with chemistries that vary widely between calcic and alkaline, magnesian and ferroan affinities. Tomson et al (2006Tomson et al ( , 2013 The SGT has been correlated with paleo-continental fragments of the Gondwana assemblage in Sri Lanka, East Antarctica and Madagascar (e.g., Plavsa et al, 2012;Li et al, 2020;Durgalakshmi et al, 2021). The Antananarivo Block of Madagascar, adjacent in Gondwana to the western Madurai Block, is also predominantly composed of Neoarchean granulites.…”
Section: Introductionmentioning
confidence: 99%